Applications to Marine Disaster Prevention Spilled Oil and Gas Tracking Buoy System - Kato, Naomi (Springer Japan : Imprint: Springer, 2017)
This book focuses on the recent results of the research project funded by a Grant-in-Aid for Scientific Research (S) of the Japan Society for the Promotion of Science (No. 23226017) from FY 2011 to FY 2015 on an autonomous spilled oil and gas tracking buoy system and its applications to marine disaster prevention systems from a scientific point of view. This book spotlights research on marine disaster prevention systems related to incidents involving oil tankers and offshore platforms, approaching these problems from new scientific and technological perspectives. The most essential aspect of this book is the development of a deep-sea underwater robot for real-time monitoring of blowout behavior of oil and gas from the seabed and of a new type of autonomous surface vehicle for real-time tracking and monitoring of oil spill spread and drift on the sea surface using an oil sensor. The mission of these robots is to provide the simulation models for gas and oil blowouts or spilled oil drifting on the sea surface with measured data for more precision of predictions of oil and gas behavior. .